2021
DOI: 10.1038/s41586-021-03983-5
|View full text |Cite
|
Sign up to set email alerts
|

Roton pair density wave in a strong-coupling kagome superconductor

Abstract: The recently discovered family of vanadium-based kagome metals with topological band structures offer new opportunities to study frustrated, correlated topological quantum states. These layered compounds are nonmagnetic and undergo charge density wave (CDW) transitions before developing superconductivity at low temperatures. Here we report the observation of unconventional superconductivity and pair density wave (PDW) in the vanadium-based kagome metal CsV3Sb5 using scanning tunneling microscope/spectroscopy (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
238
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 440 publications
(293 citation statements)
references
References 55 publications
14
238
3
Order By: Relevance
“…The A 2 mode was also observed in another Raman study [53] and by time-resolved pump-probe spectroscopy [29,54]. However, in these works, it was suggested to emerge below ∼60 K [29,53,54], hence ascribed to another phase transition associated with the unidirectional 1 × 4 order [19,31,32]. According to our data, shown in Fig.…”
Section: Cdw-induced Modessupporting
confidence: 77%
See 3 more Smart Citations
“…The A 2 mode was also observed in another Raman study [53] and by time-resolved pump-probe spectroscopy [29,54]. However, in these works, it was suggested to emerge below ∼60 K [29,53,54], hence ascribed to another phase transition associated with the unidirectional 1 × 4 order [19,31,32]. According to our data, shown in Fig.…”
Section: Cdw-induced Modessupporting
confidence: 77%
“…Indeed, charge-density waves and superconductivity have been discovered [12,15,16], with ample evidence showing that both types of orders are exotic. For example, the CDW transition is accompanied possibly by a large anomalous Hall effect [17,18], and the superconductivity features a pair-density wave state [19]. The weakly bonded layers can be mechanically exfoliated [11], enabling the exploration of the effects of dimensionality on these phenomena and their carrier-density tuning [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The superconducting state is found to be spin singlet with s-wave pairing symmetry in the bulk state [6][7][8]. STM studies observed possible Majorana modes [9] and pair density wave [10] in the surface state. There are also experimentally observed residual density of states in the superconducting state [11], which may be due to the competition between the superconductivity and the CDW [11][12][13][14][15][16].…”
mentioning
confidence: 92%